Business plan for e-Grocer: 24 Mart - Lau, Gilbert Kien Yen (2021)
Online shopping industry has been around in Malaysia for many years. The market segment for e-grocery has already grown rapidly since 2016 from its small base. According to The Star (Toh) 2017, an approximately 2% of total grocery sales were transacted online in 2017. Comparing to China and USA, the adoption of e-grocer in Malaysia was at slower rate. The main reasons are that Malaysian can easily purchase their daily grocer from nearest supermarket or wet market. In addition, Malaysian prefers “personalized services” from wet market sellers on recommendations for cooking tips and recipe and freshness of the products.